High dietary protein intake is associated with an increased body weight and total death risk. Issue 2 (April 2016) - Hernández-Alonso, Pablo; Salas-Salvadó, Jordi; Ruiz-Canela, Miguel; Corella, Dolores; Estruch, Ramón; Fitó, Montserrat; Arós, Fernando; Gómez-Gracia, Enrique; Fiol, Miquel; Lapetra, José; Basora, Josep; Serra-Majem, Lluis; et al.
Summary: Background & aims: High dietary protein diets are widely used to manage overweight and obesity. However, there is a lack of consensus about their long-term efficacy and safety. Therefore, the aim of this study was to assess the effect of long-term high-protein consumption on body weight changes and death outcomes in subjects at high cardiovascular risk. Methods: A secondary analysis of the PREDIMED trial was conducted. Dietary protein was assessed using a food-frequency questionnaire during the follow-up. Cox proportional hazard models were used to estimate the multivariate-adjusted hazard ratio (HR) and 95% confidence intervals (95%CI) for protein intake in relation to the risk of body weight and waist circumference changes, cardiovascular disease, cardiovascular death, cancer death and total death. Results: Higher total protein intake, expressed as percentage of energy, was significantly associated with a greater risk of weight gain when protein replaced carbohydrates (HR: 1.90; 95%CI: 1.05, 3.46) but not when replaced fat (HR: 1.69; 95%CI: 0.94, 3.03). However, no association was found between protein intake and waist circumference. Contrary, higher total protein intake was associated with a greater risk of all-cause death in both carbohydrate and fat substitution models (HR: 1.59; 95%CI: 1.08, 2.35; and HR: 1.66; 95%CI: 1.13, 2.43, respectively). A higher consumption of animal protein was associated with an increased risk of fatal and non-fatal outcomes when protein substituted carbohydrates or fat. Conclusions: Higher dietary protein intake is associated with long-term increased risk of body weight gain and overall death in a Mediterranean population at high cardiovascular risk. Highlights: Higher protein intake is related to a high risk of weight gain and death at long-term. Higher animal protein intake is related to fatal and non-fatal cardiovascular outcomes. No association was found between protein intake and abdominal obesity.